Pengaruh Pendidikan Perkoperasian dan Kualitas Layanan terhadap Partisipasi Anggota Koperasi Mahasiswa Universitas Negeri Surabaya di Masa Pandemi Covid-19 - Putri Ulfa Kamalia; Raudia Nur Sa'adah (Universitas Proklamasi 45, 2023)
This study examines whether cooperative education and service quality affect the participation of cooperative members. This study analyzes cooperative education and service quality as variables that can affect the participation of cooperative members. The analysis uses SPSS to test the hypothesis. The sample used was 75 respondents. The results of the study indicate that there is a positive and significant effect of cooperative education on member participation, but service quality does not affect member participation. Simultaneously, it shows that cooperative education and service quality simultaneously affect member participation.